2022
DOI: 10.3390/agriculture12101677
|View full text |Cite
|
Sign up to set email alerts
|

Root System Architecture and Omics Approaches for Belowground Abiotic Stress Tolerance in Plants

Abstract: Plant growth and productivity is negatively affected by several abiotic stresses. To overcome the antagonistic effect of a changing environment, plants have evolved several modifications at the physiological as well as molecular levels. Besides being a vital organ for a plant’s nutrient uptake, roots also plays a significant role in abiotic stress regulation. This review provides insight into changing Root System Architecture (RSA) under varying environmental stimuli using high-throughput omics technologies. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 119 publications
0
2
0
Order By: Relevance
“…The developmental switch regulating biomass/growth differences between control and treated plants is highly regulated by internal cues [ 36 ]. These regulatory components and mechanisms involved in sudden changes in the plant are not well-known.…”
Section: Discussionmentioning
confidence: 99%
“…The developmental switch regulating biomass/growth differences between control and treated plants is highly regulated by internal cues [ 36 ]. These regulatory components and mechanisms involved in sudden changes in the plant are not well-known.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in transcriptome profiles of various drought‐sensitive and drought‐tolerant genotypes have also been monitored. It is being reported that under abiotic stress, roots tend to display the expression of a greater number of transcripts as compared to leaves and shoots (Joshi et al., 2022). High‐throughput transcriptome studies have been conducted on plants subjected to drought stress, which highlighted the role of NAC‐encoding genes that are expressed in roots (Janiak et al., 2016); for instance, rice plants, overexpressing OsNAC10, had more thicker roots with enlarged epidermis and cortex (Jeong et al., 2010).…”
Section: Genes and Qtls Involved In Regulation Of The Roots Response ...mentioning
confidence: 99%